Pengaruh Isu Sosio-Saintifik dalam Meningkatkan Keterampilan Proses Sains pada Materi Larutan Elektrolit dan Non-Elektrolit - Bella Nur Farida; Sunyono Sunyono; Tasviri Efkar (Universitas Lampung, 2019)
This research was aimed to describe the effect of socio-scientific issues on improving science process skills. The method used was quasi-experiment with pretest-postest control group design. The samples were X MIA 4 as experiment class and X MIA 3 as control class, cluster random sampling technique was used in determining the samples. The effect of socioscientific issues was analyzed using the difference between two average tests and the effect size test. The results of the research show that the science process skills of students in the experiment class were higher than in the control class. The effect size of socio-scientific issues as a